A blessing for Miriam [large type] - Eicher, Jerry S. (Eicher, Jerry S. Land of promise, 2015)
Miriam Yoder is looking forward to her wedding day with Wayne Yutzy. But when beautiful Esther Swartz arrives, Miriam is wary of their past relationship. When storms rip through their small Amish community, Miriam's daett arrives to help in the rebuilding efforts and upends her relationship with Wayne. Must Miriam now build her new life as a single Amish woman?